Beyond the Gates: Identifying and Managing Offenders with Attention Deficit Hyperactivity Disorder in Community Probation Services - Young Susan; Gudjonsson Gisli H; Goodwin Emily; Jotangia Amit; Farooq Romana; Haddrick David; Adamou Marios (AIMS Press, 2014)
Research has indicated that, compared with the general population, the prevalence of offenders with ADHD in prison is high. The situation for offenders managed in the community by the Probation Service is unknown. This study aimed to bridge the gap in our knowledge by (1) surveying the awareness of probation staff about ADHD and (2) screening the rate of offenders with ADHD managed within the service. In the first study, a brief survey was circulated to offender managers working in 7 Probation Trusts in England and Wales asking them to estimate the prevalence of offenders with ADHD on their caseload, the presenting problems of these offenders and challenges to their management, and the training received on the treatment and management of offenders with ADHD. The survey had a return rate of 11%. Probation staff perceived that 7.6% of their caseload had ADHD and identified this group to have difficulties associated with neuropsychological dysfunction, lifestyle problems and compliance problems. They perceived that these problems hindered meaningful engagement with the service and rehabilitation. Challenges to their management were perceived to be due to both internal processes (motivation and engagement) and external processes (inadequate or inappropriate interventions). Few respondents had received training in the management of offenders with ADHD and most wanted more support. In the second study, a sub-sample of 88 offenders in one Probation Trust completed questionnaires to screen for DSM-IV ADHD in childhood and current symptoms. The screen found an estimated prevalence of 45.45% and 20.51% for childhood and adulthood ADHD respectively and these were strongly associated with functional impairment. Thus probation staff considerably underestimated the likely rate, suggesting there are high rates of under-detection and/or misdiagnosis among offenders with ADHD in their service. The results indicate that screening provisions are needed in probation settings, together with training for staff.